Jogkorlátozás és jogfosztás a gazdasági életben a Pécsi Királyi Törvényszék gyakorlata alapján (1938–1944) - Herger, Csabáné (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The goal of this study, based on the remained documents of the cases started in 1942 at the Royal Tribunal of Pécs, is to examine the legal disputes concerning contracts of sales which does and does not constitute commercial transactions in the southern Transdanubia, Baranya county, Hungary, and how the right restrictions and deprivations of the Horthy era appeared in them. The study also aims to show the types of crimes connected to commercial activities which were partially created by the extraordinary legislation as a result of the war.